The Role of Metformin in patients with Primary Hypothyroidism - Al-Lehibi, Khalid Ibrahim (AL-Kindy College Medical Journal, 2019)
Background: Insulin resistance is present in 50% or more of patients with primary hypothyroidism. Metformin can decrease TSH levels in these patients by a complex matter, this can be of great help in clinical practice.Objective: This study was designed to evaluate the effect of metformin in reducing TSH levels in patients with primary hypothyroidism.Methods: Hundred patients with primary hypothyroidism, 82 females, 18 males were included in this study, everyone was followed up for two months after adding metformin 850 mg twice daily in addition to thyroxin.Results: 36 patients (36%) have a normal baseline TSH and no change after 2 months, 64 patients (64%)have a change in TSH either a decrease(49 patients ,79.56%) or an increase (15 patients , 23.44 % ).Conclusion: Metformin therapy is highly effective in reducing TSH levels in patients with primary hypothyroidism.